Innovation Flashback (Research technology management, 2017)
The club served as a kind of incubator for Silicon Valley; a number of microcomputer companies, entrepreneurs, hackers, and other tech stars emerged from its ranks-most famously Apple. MARCH 7, 1876-Alexander Graham Bell files a patent for the telephone, beating a similar claim by just two hours. Bell sued Gray and Western Union for infringement, taking the case all the way to the US Supreme Court, which upheld Bell's right to the invention.